Assessment of the Implementation of Lung Cancer Consensus Statements From the Royal College of Radiologists in 2021; Progress and Barriers. Issue 11 (November 2022) - McAleese, J.; Tumelty, K.; Baluch, S.; Powell, C.; Drinkwater, K.
Abstract: Background: Lung cancer outcomes in the UK are worse than those in many similar countries. The RCR developed a series of 43 consensus statements (CS) to facilitate improvements in care for patients treated with radiotherapy. Methods: We asked all 61 UK radiotherapy centres to self-assess the implementation of the CS and to describe their departmental key strengths and weaknesses in September 2021. Results: 87% of centres returned their assessments. Whilst developmental activity was seen in most areas for most centres, 24 of the statements were felt to be difficult to implement within the next 2 years by at least one centre. The most frequently reported strengths were in the implementation of SABR (stereotactic body radiotherapy), concurrent chemoradiation for non-small cell lung cancer and technological aspects of treatment planning. The most frequently described departmental weaknesses were in pre-habilitation, timeliness of PET/CT scans and prophylaxis for Pneumocystis jiroveci Pneumonia (PJP). Barriers to implementation were often due to insufficient resource, a requirement for organisations to work together, and a perceived lack of evidence base. Strengths were often attributed to good team working, a local champion and being an early adopter. Conclusions: This work confirms the commitment of lung cancer radiotherapy teams across the UK to improve outcomes for their patients. Most of the statements have been implemented at least partially. Themes have been identified to aid further progress, one of which is a requirement for significant investment.